A study of the translation of fairy tales from english into vietnamese – a cognitive sociolinguistics perspective - Trần Thị Xuân Thắm (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
There have been many fairy tales in English translated into Vietnamese. A problem that should be taken into consideration is whether the translational versions convey all of the specific characteristics of the original tales or whether English learners in Vietnam find it useful to improve their knowledge by reading bilingual fairy tales. Based on the theories of Cognitive Sociolinguistics, this study makes an investigation into English fairy tales in an attempt to find out the typical features that make English fairy tales different from other genres of literature. Another linguistic theory employed in the thesis is the one of translation. For data analysis, contrastive and inductive methods have been used.The study found that besides the achievements obtained, there are some problems that should be pointed out. This study suggests three kinds of errors defined as under-translation, over-translation and unnaturalness found to be common in the translational versions. The findings then serve as a foundation to put forward some possible suggestions for Vietnamese translators and some implications for Vietnamese learners of English.